Aberrant demethylation and expression of MAGEB2 in a subset of malignant peripheral nerve sheath tumors from neurofibromatosis type 1. Issue 2 (February 2016) - Nobeyama, Yoshimasa; Nakagawa, Hidemi
Highlights: MAGEB2 was analyzed for tumors from neurofibromatosis type 1 patients. MAGEB2 is methylated in normal Schwann cells and any types of neurofibroma. MAGEB2 can be aberrantly demethylated in malignant peripheral nerve sheath tumors. MAGEB2 can be aberrantly expressed in malignant peripheral nerve sheath tumors. Abstract: Background: Malignant peripheral nerve sheath tumors (MPNSTs) occur in several percent of neurofibromatosis type 1 (NF-1) patients. When a CpG island (CGI) in the 5' region of a gene is methylated, transcription of that gene may be suppressed. Although cancer-testis antigens, including MAGEB2, are potential therapeutic targets for cancer in medical practice, information on MAGEB2 in MPNST is scarce. Objective: The purpose is to clarify the methylation status and expression of MAGEB2 in MPNSTs derived from patients with NF-1. Methods: Quantitative real-time methylation-specific PCR (RT-MSP) and quantitative real-time reverse transcription-PCR (RT-PCR) were performed to measure methylation and mRNA expression, respectively, in MPNST cell lines and in MPNST and neurofibroma samples from patients with NF-1. Immunohistochemical analysis was also performed to assess MAGEB2 protein expression. Results: RT-MSP and RT-PCR data showed low methylation levels and detectable mRNA expression of MAGEB2, respectively, in one MPNST cell line, but high methylation level and absence of expression in each other cell line and in normal cells. Based on RT-MSP data, 3 of 18 MPNST clinical samples exhibited low methylation levels; in contrast, all cutaneous and plexiform neurofibroma samples and normal cells exhibited high methylation levels. Methylation levels were not significantly associated with any clinical parameters. Immunohistochemical analysis revealed expression of MAGEB2 protein in MPNST clinical samples with the low methylation level. Conclusions: MAGEB2 can be aberrantly demethylated and expressed in MPNSTs. Conversely, the gene may not be demethylated in any types of neurofibroma, suggesting that the demethylation does not occur before malignant transformation.